Characteristics of acute groin injuries in the adductor muscles - a detailed MRI study in athletes - Serner, A.; Weir, A.; Tol, J. L.; Thorborg, K.; Roemer, F.; Guermazi, A.; Yamashiro, E.; Hölmich, P. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Acute adductor injuries account for the majority of acute groin injuries; however, little is known about specific injury characteristics, which could be important for the understanding of etiology and management of these injuries. The study aim was to describe acute adductor injuries in athletes using magnetic resonance imaging (MRI). Male athletes with acute groin pain and an MRI confirmed acute adductor muscle injury were prospectively included. MRI was performed within 7 days using a standardized protocol and a reliable assessment approach. 156 athletes presented with acute groin pain of which 71 athletes were included, median age 27 y (range 18-37). There were 46 isolated muscle injuries, and 25 athletes with multiple adductor injuries. In total, 111 acute adductor muscle injuries were recorded; 62 adductor longus, 18 adductor brevis, 17 pectineus, 9 obturator externus, 4 gracilis and 1 adductor magnus injury. Adductor longus injuries occurred at three main injury locations; proximal insertion (26%), intramuscular musculotendinous junction (MTJ) of the proximal tendon (26%) and the MTJ of the distal tendon (37%). Intramuscular tendon injury was seen in 1 case. At the proximal insertion 12 of 16 injuries were complete avulsions. This study shows that acute adductor injuries generally occur in isolation from other muscle groups. Adductor longus is the most frequently injured muscle in isolation and in combination with other adductor muscle injuries. Three characteristic adductor longus injury locations were observed on MRI, with avulsion injuries accounting for three quarters of injuries at the proximal insertion, and intramuscular tendon injury was uncommon.